The Cancer Burden in Sarawak, Malaysia: Sarawak Cancer Report - Shirley Siang Ning Tan; Lee Len Tiong; Kung Yee Wong; Mastulu Binti Wahab; Alan Yean Yip Fong; Choo Huck Ooi (Health Science Reports)
ABSTRACT Background and Aims Malaysia, like many developing countries, is undergoing epidemiologic transition where non‐communicable diseases, including cancer, are emerging as a prevalent health burden. Sarawak is the largest state in Malaysia, located on the island of Borneo. Compiling region‐specific cancer statistics is crucial for future planning and implementation of effective cancer management strategies. Methods This study utilized cancer data reported to the Sarawak State Health Department with a cancer notification form. Data was obtained from the State cancer database. Incidence, Age‐Standardized Rate, frequency, cumulative rate, and lifetime risk were calculated. The population included Sarawak residents only who were defined as Malaysian citizens as well as permanent residents living in Sarawak at the time of diagnosis. Results Between years 2011–2015, there were a total of 10,320 cancer cases (47.3% male). The incidence rate was approximately 16.6 persons per 100,000 population per year. An increasing trend was observed in cancer incidence with increasing age. Ethnic distribution reported the highest incidence among the Chinese (male cases:36.2% and female cases:36.4%), followed by the Iban (male cases:26.9% and female cases:24.5%), and Malay (male cases:18.3% and female cases:22.0%). The three most common cancers in male were colorectal (15.4%), nasopharyngeal (14.8%), and trachea, bronchus, lung (14.0%) cancer. In females, the first three common cancers were breast (27.9%), cervix uteri (11.6%), and colorectal (9.8%). There were wide disparities among common cancers across genders, different age groups and ethnic groups. Conclusion The lifetime risk of a Sarawakian to develop cancer by age 75 is 1 in 11 in females and 1 in 10 in males. This present study provided a framework for the status and trend of cancer in Sarawak. These findings will provide additional information to guide strategy and resource planning in improving cancer care in Sarawak.